Combined Treatment of Native Femoropopliteal Occlusions in Chronic Limb-Threatening Ischemia Using Atherectomy Debulking and a New Sirolimus Drug-Coated Balloon (SELUTION SLR) - Joseph Sumner; Sajal Patel; Iakovos Theodoulou; Narayanan Thulasidasan; Panos Gkoutzios; Irfan Ahmed; Athanasios Saratzis; Athanasios Diamantopoulos (The Arab Journal of Interventional Radiology)
Objective The aim of this study was to report the primary outcomes of a pilot study investigating the safety and efficacy of sirolimus drug-coated balloons (SELUTION) for endovascular postatherectomy treatment of native occluded femoropopliteal lesions in patients with chronic limb-threatening ischemia (CLTI).